2021
DOI: 10.1097/ico.0000000000002866
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Dupilumab-Induced Ocular Surface Disease in Adults With Atopic Dermatitis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Clinical trials and daily practice studies of dupilumab‐treated AD patients reported DAOSD incidences of up to 34%, which is more or less comparable to our incidence 2–4 . The most frequently observed ophthalmological characteristics were conjunctivitis (both bulbar and tarsal), blepharitis and Meibomian gland dysfunction, both before and during dupilumab treatment, which is partly in line with previous literature 16–18 . However, the majority of studies regarding DAOSD are not based on ophthalmological data, but on patient‐reported diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical trials and daily practice studies of dupilumab‐treated AD patients reported DAOSD incidences of up to 34%, which is more or less comparable to our incidence 2–4 . The most frequently observed ophthalmological characteristics were conjunctivitis (both bulbar and tarsal), blepharitis and Meibomian gland dysfunction, both before and during dupilumab treatment, which is partly in line with previous literature 16–18 . However, the majority of studies regarding DAOSD are not based on ophthalmological data, but on patient‐reported diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical findings of DIOSD in our cases were characterized by severe conjunctival hyperemia with conjunctival swelling in the palpebral and bulbar conjunctiva, which was the same as previously reported [ 4 , 5 , 10 , 11 ]. However, these conjunctival findings are not specific to DIOSD, and the differential diagnosis of acute exacerbation of AKC is difficult.…”
Section: Discussionsupporting
confidence: 88%
“…Dupilumab-induced blepharitis and conjunctivitis have a wide variety of clinical phenotypes including moderate to severe conjunctivitis [ 4 ], follicular conjunctivitis [ 5 ], giant papillary conjunctivitis [ 6 , 7 ], blepharoconjunctivitis [ 8 ], cicatrizing conjunctivitis [ 9 ], and corneal limbitis [ 5 ]. Therefore, ocular surface diseases that occur during dupilumab treatment have been names dupilumab-induced ocular surface diseases (DIOSDs) [ 10 , 11 ]. However, the detailed pathogenesis of DIOSD is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…We identified clinical findings of DAOSD that are uncommon in the literature. 23 A significant proportion of our patients presented with limbal nodules, sometimes accompanied by Horner-Trantas-like dots. This form of limbal inflammation may be seen in the limbal form of vernal keratoconjunctivitis, but it is very rarely encountered in our geographic area and is also less common in adults.…”
Section: Discussionmentioning
confidence: 74%
“…The largest cohort included 210 patients with AD and examined the onset of DAOSD in general. 23 They identified 78 patients as having developed DAOSD, among whom 15 patients were seen in ophthalmology. Other large case series included 10–23 patients and described the clinical manifestations of DAOSD as being predominantly characterised by eyelid dermatitis, blepharitis, limbal inflammation and conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%